اثر سياسة النقد الأجنبي على المستوى العام للأسعار: دراسة تطبيقية في السودان للفترة من (2011) 2015 ) - د. موسى عبدالله محمد (White Nile Journal for Studies and Research, 2017)
Foreign exchange polices in Sudan an important Role and influential on general economic activity and the banking system. As well as banks in the foreign exchange market. Acting for this role in attracting foreign Cash resources and contribute to the local needs of foreign currencies. The study aims to identify the impact offoreign Cashpoliciesand itsrole in general price level in Sudan and in drawing implementing policies. The problem of the study liesin the lack offoreign Cash to the, that helps to meet the obligations andhelps to stabilize local currency. Cycle which is reflected on the pricelevel in Sudan. The study was conducted (inductive and deductive andanalysis) approach so the most important finding of the researcher; food commodities (sugar, vegetable, oils and dairy products). Andthe adoption of Sudan on the important of these goods. It requires that your provide measure of foreign Cash and which is reflected on higher pricesin Sudan and the most important recommendation you must make a real effort to stimulate the exports and to work on structural reform of the economy and Production and producing Increase, quality for free completion in international markets